The Meaning of Income in The Perspective of Patience Traders During The 2019 Corona Virus Disease Pandemic - Laylin Hamdiyah; Rahmat Agus Santoso (INNOVATION RESEARCH JOURNAL, 2022)
Traders at Balongpanggang Traditional Market experienced a decrease in income during the 2019 corona virus disease pandemic. Traders at Balongpanggang Traditional Market still earned income, although not as much as before the 2019 corona virus pandemic. Traders remained steadfast in facing a decline in income, remained diligent in running their business even though their income has decreased and remains steadfast in their stance and does not give up easily in obtaining income. This study aims to find out why the traders in Balongpanggang Market are steadfast, persevering and face a decline in income. By collecting data from 8 informants and 1 key informant as an opening research to find accurate results. The presentation of the data is carried out using data analysis, namely data reduction, data display and drawing conclusions. The results of data analysis on traders' income during the 2019 corona virus disease pandemic were very large, but the traders at Balongpanggang Traditional Market remained firm in their stance in running their business because of their expertise and motivation. Traders in Traditional Markets also remain steadfast in the face of declining incomes for family welfare and happiness. In addition, the traders at the Balongpanggang Traditional Market continue to run their business by monitoring the selling of merchandise and never giving up to earn income.